Cultivation of Chlorella sp. as Biofuel Sources in Palm Oil Mill Effluent (POME) - Hadiyanto, H; Azimatun Nur, Muhamad Maulana; Hartanto, Ganang Dwi (Center of Biomass & Renewable Energy, Diponegoro University, 2012)
Renewable energy is essential and vital aspect for development in Indonesia especially less oil reserve for coming 15 years. Biodiesel has received much attention as renewable energy in recent years. One of potential biodiesel is produced from microalgae. Due to high content of nutrients in Palm Oil Mill Effluent (POME), this waste is a potential for nutrient growth for microalgae. Chlorella is one of high potential for biodiesel since it has high lipid content (20-30%). The objective of the research is to determine growth rate and biomass productivity in Chlorella Sp cultured in POME. Chlorella Sp was cultured in 20%, 50%, 70% POME using urea concentration 0.1gr/L (low nitrogen source) and 1gr/l (high nitrogen source) at flask disk, pH 6.8-7.2; aerated using aquarium pump and fluorescence lamp 3000-6000 lux as light. Medium was measured using spectrophotometer Optima Sp-300 OD at 680 wave length in 15 days to calculate specific growth rate. At end of cultivation, Chlorella sp was filtered and measured as dry weight. Result indicated that Chlorella sp at 50% POME 1gr/L urea showed higher specific growth rate (0.066/day). Factor affecting growth rate of microalgae is CNP ratio, POME concentration, and urea concentration.